Bird community effects on avian malaria infections - Juliana Tamayo-Quintero; Josué Martínez-de la Puente; Miriam San-José; Catalina González-Quevedo; Héctor F. Rivera-Gutiérrez (Scientific Reports, 2023)
Abstract In community assembly processes, interspecific interactions play an important role in shaping community diversity, especially at the local scale. Changes in species richness or abundance can modify local infectious disease dynamics, either reducing or increasing the risk of transmission within the community. This study evaluates the effects of bird community on avian haemosporidians infections in a Neotropical region. Bird samples were collected from areas surrounding three dams, and molecular analysis were performed to identify blood-parasitic haemosporidia infecting the birds. Generalized linear models were used to analyze the relationships between the bird community and the prevalence, number of infections, and richness of avian haemosporidian lineages. Non-significant effects of bird community dominance and richness on the prevalence of avian parasites and the number of infections of Haemoproteus were found. However, there was evidence of an amplification effect. Host dominance was associated with the total number of infections, the number Plasmodium infections and the expected richness of Plasmodium lineages, while the expected richness of Haemoproteus lineages was associated with the richness of bird species. These findings highlight the role of host community dominance and richness in the dynamics of parasite infections, potentially influenced by the availability of competent hosts. This study contributes significantly to our understanding of blood parasite diversity in tropical birds within a relatively understudied region of South America.